Facial Skeletal Reconstruction with Porous Polyethylene Implants: Case Report - Ayse Gülşen; Fulya Fındıkçıoğlu; Reha Yavuzer (Turkish Journal of Orthodontics, 2010)

(untitled)
Reconstruction of facial contours with facial implants are procedures done simultaneously with orthognatic surgery or as an isolated procedure in order to get a good facial esthetics and patient satisfaction better. The results of bioimplants are good with few complications, If they applied properly. In this study, two cases whose facial contours are supported by ‘porous polyethylene implants' were presented.